From Traditional Game to Mathematical Representation: An Ethnomodelling Study of Congklak - Sri Suryanti; Clinton Chidiebere Anyanwu (Universitas Negeri Surabaya, 2026)
This research examines congklak game as a local practice involving mathematics and represents mathematical aspects of the congklak using ethnomodeling approach. Using qualitative methods with an interpretive ethnographic design, data were gathered through observations of congklak players, documentation of congklak paraphernalia, and analysis of seed arrangement on the congklak board. The analysis followed emic, etic, and dialogic stages to translate local gameplay practices into formal mathematical representations. Results showed that congklak includes mathematical aspects such as enumeration, discrete distribution, one-to-one relationship, cycles, positionality, conservation of quantity, and transformations from one board position to another. Congklak mathematical structures were then represented mathematically in the form of cyclic discrete position systems, distribution function that leads to final board position, and transformations of game positions. Findings show that congklak cannot simply be described as a form of play or learning situation that takes place in a cultural context; it is also a local body of knowledge having mathematics in its operations. Ethnomodeling is further advanced as an analytical approach in lieu of descriptive ethnomathematics while acknowledging local culture as the basis of contextualized mathematics education.